O laço possível: considerações sobre a transferência na clínica da paranoia - Tuliola Almeida de Souza Lima (2011)
This dissertation aims to expose certain principles for clinical psychoanalysis of paranoia, specifically regarding the maneuver of transference. We begin presenting a clinical case followed in a psychiatric ambulatory, whose paranoia diagnosis was drawn with some certainty, but whose maneuver required clarification regarding the functioning of the psychic structure in question. Therefore, the first chapter explicits paranoias clinical manifestation, using Freuds and Lacans theories on the subject. Afterwards, we analyze the phenomenon of transference, establishing how it occurs in neurosis and its particularities in paranoiac psychosis. Using the bibliography on this theme and also some fragments on the analysts position in such treatments, we trace the maneuver possibilities, in which the analyst answers the structure trying to avoid a position that serves to increment the patients delirium. The maneuver consists in keep the link without letting the analyst become the representation of an Other who aims at the subject. We observe the inflation of the imaginary as result of a surge and we attribute its condition of occurrence to a lack in the symbolical. The intention of someone who starts to follow the subject, or to love him/her and to search for him/her, is understood as an incarnation of the Others demand for enjoyment, of which the paranoid subject becomes the object. That is what characterizes the eruption of the real, sometimes leading the patients to look for treatment. We establish that one of its aims is to rectify the Other in a way that the subject starts do deal with a new symbolical reference, contributing to his/her identification in this relation. The hypothesis that takes us to the third chapter passes by this localization of the subject in front of the Other, which allows a form of stabilization and possibly an insertion in the social bonds. We observe that the turnouts guided by the imaginary not always allow a long lasting solution for the subjects. That is why the treatment functions as a tool for this decompensation by showing itself as a space for the subject to address his/her particular solutions, sometimes more or less stable, depending on each case. Lacanian theory is our reference, which we use not only as a parameter for the present work, but also as a guide for the treatment realized at the ambulatory. The bibliography used goes beyond psychoanalysis classic references, passing by authors of lacanian orientation who have clinical experience with paranoia - a field in which we found many published works. In the end of the dissertation, we approach the mode of treatment of psychosis referenced by a mental health institution, whose model has consolidated itself presently, comparing its functioning with the introduction of a new figure of the Other that gives space for the solution of each paranoiac subject. The bid we make is that the psychoanalytical treatment of psychosis, with adequate transference maneuver, allows some stabilization for a determined subject.